Relocation in space, language, and identity: Dislocated North Korean undergraduates in South Korean universities. (March 2016) - Lee, Mun Woo; Ahn, Sung-Ho G.
Abstract: This study examines how dislocated North Korean undergraduates enrolled in South Korean universities interact with their South Korean peers and construct their own identities. Data were collected based on records of meetings between students, short reflection journals completed after each of these meeting, and semi-structured individual interviews. During their interactions with South Korean students, the North Korean students agreed with their South Korean peers unconditionally, hid their North Korean accents, and avoided North Korean-related topics. These interaction patterns were directly related to their "peripheral" positioning in South Korean society. They placed an emphasis on proficiency in spoken English and viewed themselves as "deficient in that language, and thus, inferior". This study clarifies the underlying language ideologies in South Korea and how such macro-level structures are intertwined with language practices and identity formation among disempowered transmigrants, such as dislocated North Korean undergraduates. Highlights: Dislocated North Korean undergraduates in South Korean universities. One on one interaction between North Korean students and South Korean students. North Korean students' unconditional agreement with South Korean students. North Korean students' avoidance of North Korea-related topics. North Korean students' peripheral self-positioning.